DAMPAK TEKNOLOGI DIGITAL, AI, DAN STRATEGI PROMOSI TERHADAP EFISIENSI DAN PRODUKTIVITAS INDUSTRI PARIWISATA - Arya Kusuma, Bagus (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2025)
Digital transformation has become a critical factor in enhancing the competitiveness of the global tourism industry, including in Bali as one of Indonesia’s leading destinations. In the face of increasing demands for efficiency and productivity, the adoption of digital technology, artificial intelligence (AI), and adaptive promotional strategies has emerged as a key to operational success. This study aims to examine the influence of these three factors on efficiency and productivity in the tourism industry. Using a quantitative explanatory research design, data were collected through a structured survey involving 60 members of the Regional Board of the Indonesian Hotel and Restaurant Association (DPD PHRI Bali), and analyzed using multiple linear regression in SPSS version 26. The results show that digital technology, AI, and promotional strategies significantly affect efficiency and productivity simultaneously (R² = 0.743; F = 54.014; p < 0.001). Promotional strategy has the strongest partial effect (β = 0.442), followed by digital technology (β = 0.302) and AI (β = 0.286). These findings emphasize the importance of integrated digital tools and strategic communication in boosting performance. This study contributes to technology-based tourism literature and provides actionable insights for practitioners and policymakers to enhance competitiveness through efficient digital adoption and targeted promotions. Further research is recommended to include broader variables and different regional scopes.